Autophagy Genes and Otitis Media Outcomes - Yong Jun Kim; Hwa Sung Rim; Jeong Hee Kim; Sung Soo Kim; Joon Hyung Yeo; Seung Geun Yeo (Clinics and Practice, 2024)
Otitis media (OM) is a common cause of hearing loss in children that requires corrective surgery. Various studies have investigated the pathomechanisms and treatment of OM. Autophagy, an essential cellular recycling and elimination mechanism implicated in various diseases, is known to play an important role in the pathogenesis of OM. Here, we conducted a literature review on autophagy in OM, highlighting the relationship between expression patterns of autophagy-related factors and pathophysiological and clinical aspects of OM. We summarized the existing research results on the expression of autophagy-related factors in acute OM (AOM), OM with effusion (OME), chronic OM (COM) with cholesteatoma, and COM without cholesteatoma (CholeOM) in animals and humans. Autophagy-related factors are expressed in the middle ear mucosa or fluid of AOM, effusion of OME, granulation tissue of COM, and cholesteatoma of CholeOM. Among ATGs and other autophagy-related factors, the most extensively studied in relation to the pathogenesis of OM are mTOR, LC3II/I, PI3K, Beclin-1, FLIP, Akt, and Rubicon. Expression of autophagy-related factors is associated with AOM, OME, COM, and CholeOM. Inadequate expression of these factors or a decrease/increase in autophagy responses can result in OM, underscoring the critical role of ATGs and related factors in the pathogenesis of OM.